2011
DOI: 10.3233/ch-2010-1362
|View full text |Cite
|
Sign up to set email alerts
|

Blood viscosity changes in slow coronary flow patients

Abstract: Microvascular dysfunction is implicated in the pathogenesis of slow coronary flow (SCF), but less attention has been paid to intrinsic properties of blood that can also impair the microcirculatory flow. In this study we aimed to evaluate the blood viscosity focusing on erythrocyte aggregation, erythrocyte deformability and plasma viscosity in SCF. Thirty-three patients with SCF (21 male, 54 ± 12.8 years) and 23 subjects with normal coronary arteries (13 male, 59 ± 10.3 years) were included in the study. Corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Previous studies have shown an increased viscosity in patients with coronary slow flow at angiography [8], and the existence of a strong correlation between blood viscosity and MPV [28]. In our dataset, hematocrit was strongly associated with TIMIfc and was independent of endothelial function and platelet parameters across a wide range of TIMIfc.…”
Section: The Impact Of Hemorheological Parameterssupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown an increased viscosity in patients with coronary slow flow at angiography [8], and the existence of a strong correlation between blood viscosity and MPV [28]. In our dataset, hematocrit was strongly associated with TIMIfc and was independent of endothelial function and platelet parameters across a wide range of TIMIfc.…”
Section: The Impact Of Hemorheological Parameterssupporting
confidence: 65%
“…Further, blood samples were processed immediately after collection in order to limit the impact of storing on hemorheological parameters. Finally, the role of platelet, erythrocyte and leukocyte aggregability has been previously demonstrated [8,13] and was not studied here.…”
Section: Limitationsmentioning
confidence: 96%
“…The aggregation amplitude may be more sensitive than the aggregation index. It has been indicated that the aggregation amplitude is significantly higher in patients with slow coronary flow, whereas there was no significant difference between the groups with respect to the aggregation index [ 30 ]. In another study, Hazer et al demonstrated the effect of pravastatin on hemorheological parameters in a rodent traumatic brain injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Hb concentration is a determinant of blood viscosity, and a significant relationship between CSF and Hb concentration has been demonstrated previously [ 11 ]. The SCF patients frequently present with elevated blood viscosity [ 23 ]. Similar to atherosclerosis, blood viscosity is elevated in SCF patients as a result of increased platelet adhesion to the subendothelium, elevated protein infiltration into the arterial wall, and alterations to local shear forces [ 24 ].…”
Section: Discussionmentioning
confidence: 99%